Experimental study on active tuned inerter-dampers: Application to active damping using force feedback. (8th December 2021) - Zhao, Guoying; Paknejad, Ahmad; Raze, Ghislain; Deraemaeker, Arnaud; Kerschen, Gaetan; Collette, Christophe
Highlights: An active inerter-damper based on force feedback is proposed. Simple expressions of the optimal settings of the controller are obtained. The equivalent mechanical model of the proposed controller is developed. The theoretical study is experimentally validated. Abstract: In this paper, a modified active tuned inerter damper concept which is more suitable for practical applications is proposed. The proposed device is composed of a pair of collocated reactive actuator and force sensor. A second-order low-pass filter and a proportional term are combined to form the controller. The equivalent mechanical model of the controller's components is derived in order to better interpret the coupled system. The second-order low-pass filter is mechanically equivalent to a pure mechanical network which comprises an inerter, a spring and a damper connected in parallel. The proportional term mechanically represents a spring which is connected in series with the inherent actuator spring. Simple regressions are derived based on the ℍ∞ optimisation criterion wherein the optimal feedback gains are calculated to minimise the maximal response of the driving-point receptance of the system. The numerical study is also experimentally validated. The obtained results are found to correspond well with the theoretical developments.